ROMAN COARSE POTTERY FROM CIBALAE: A TYPOLOGY - Ožanić Roguljić, Ivana (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper presents the finds of Roman coarse pottery found on four different sites in the town of Vinkovci (Croatia), the Roman Cibalae (Vinkovci-Šokadija, Vinkovci-Varteks, Vinkovci-Muzej and Vinkovci-Komercijalna banka). All of them are situated on the Eastern side of the forum of Cibalae, and can be considered as parts of the same complex. The stratigraphy of sites has been ruined during the extensive urban development of Vinkovci in the 20th century. During the excavations of those sites 3,883 shards of pottery were found. The analysis provided an overview of the different pottery classes used during four centuries, i.e. from the 1st to the 4th century AD, when the city of Cibalae flourished as an important urban centre. In this work we concentrate on the coarse pottery. The coarse pottery is the most widespread class of pottery (36%). The coarse pottery from Cibalae is rough in texture; the prevailing colours are dark grey and dark brown, sometimes almost black with darker margins and surfaces. In fabric there are some evidences of multicoloured quartz, fine mica and flint inclusions. This type of pottery is locally made and it is used for food preparation, cooking and storage. The forms found in Cibalae come in different kinds of bowls, tripod bowls, pots, lids and a strainer. Most of the finds range in date from the mid 1st to the end of the 2nd century. Some types date from the 2nd to the 4th centuries. Bowls (CPB coarse pottery bowl) are present in eight different types. There are six types of pots (CPP coarse pottery pot) and just one type of lid (CPL coarse pottery lid) and strainer (CPS coarse pottery strainer).